The two latin cultures and the foundation of renaissance humanism in medieval Italy - Witt, Ronald G. (Cambridge University Press, 2012)
"This book traces the intellectual life of the Kingdom of Italy, the area in which humanism began in the mid-thirteenth century, a century or more before exerting its influence on the rest of Europe. Covering a period of over four and a half centuries, this study offers the first integrated analysis of Latin writings produced in the area, examining not only religious, literary, and legal texts. Ronald G. Witt characterizes the changes reflected in these Latin writings as products of the interaction of thought with economic, political, and religious tendencies in Italian society as well as with intellectual influences coming from abroad. His research ultimately traces the early emergence of humanism in northern Italy in the mid-thirteenth century to the precocious development of a lay intelligentsia in the region, whose participation in the culture of Latin writing fostered the beginnings of the intellectual movement which would eventually revolutionize all of Europe"--